Thar Mahima: an improved cultivar of muskmelon identified for arid region (IASH Indian Journal of Arid Horticulture, 2024)
The ‘Thar Mahima’ cultivar of muskmelon along with nine genotypes including checks was evaluated at ICAR-CIAH, Bikaner for 3 consecutive summer years (2016, 2017 and 2018) replicated thrice. The experiments were conducted following the recommended package of practices for muskmelon cultivation. From the results, it is evident that ‘Thar Mahima’ cultivar showed promising performance with respect to first fruit picking (75-80 DAS), high TSS (11.58-11.80%), fruits weighing 780-900 g with 2.8-3.2 cm thick flesh having salmon orange colour, 0.30 0.48 cm thick rind and small seed cavity (2.8-3.2 cm). It produced 4-5 fruits per plant which were round and attractive with netted surface having sutures.